Identifying Structural Reform Gaps in Emerging Europe, the Caucasus, and Central Asia - Funke, Norbert (IMF Working Papers; Working Paper, 2017)
Using data from the World Economic Forum's Global Competitiveness Report as an example, this paper compares structural indicators for 25 countries in Emerging Europe, the Caucasus, and Central Asia with a generic country with similar charactersitics that is 40 percent richer as well as a country with the average EU income. This comparison suggests that improvements will be particularly crucial in the areas of institutions, financial market development, infrastructure, goods and labor market efficiency and areas related to innovation. For the generally more ambitious goal of reaching average EU income, the reform needs are correspondingly larger. The methodology focuses on (approximate) comparisons between countries and does not try to establish the link between structural reforms and growth. While we test for changes in empirical specifications, caveats relate to the quality of structural indicators, possible non-linearities, and reform complementarities. The approach can be applied to other indicators and at a more granular level.